Neighborhood characteristics as determinants of healthcare utilization: a theoretical model - Mohnen, Sigrid M.; Schneider, Sven; Droomers, Mariël (Health economics review, 2019)
Background: We propose using neighborhood characteristics as demand-related morbidity adjusters to improve prediction models such as the risk equalization model. Results: Since the neighborhood has no explicit ‘place’ in healthcare demand models, we have developed the “Neighborhood and healthcare utilization model” to show how neighborhoods matter in healthcare utilization. Neighborhood may affect healthcare utilization via (1) the supply-side, (2) need, and (3) demand for healthcare – irrespective of need. Three pathways are examined in detail to explain how neighborhood characteristics influence healthcare utilization via need: the physiological, psychological and behavioral pathways. We underpin this theoretical model with literature on all relevant neighborhood characteristics relating to health and healthcare utilization. Conclusion: Potential neighborhood characteristics for the risk equalization model include the degree of urbanization, public and open space, resources and facilities, green and blue space, environmental noise, air pollution, social capital, crime and violence, socioeconomic status, stability, and ethnic composition. Air pollution has already been successfully tested as an important predictive variable in a healthcare risk equalization model, and it might be opportune to add more neighborhood characteristics.
Gesehen am 14.06.2019
Keywords: Aufsatz in Zeitschrift